Rapid risk assessment to prioritise potentially high-risk non-native plant pests to protect agriculture and forestry, safeguard biodiversity, and facilitate trade in Burundi - Mulema, Joseph; Ndayihanzamaso, Privat; Birushe, Placide; Bizimungu, Epitace; Cimpaye, Eustache; Gikoro, Elie; Hakizimana, Gaspard; Hatungimana, Egide; Ingabire, Arlène; Irakiza, Antoine; Itangishaka, Marie Goreth; Manirakiza, Michel; et al. (Frontiers in Agronomy, 2025)
The lack of information regarding potential invasions is one of the crucial factors contributing to the rise in pest incursions in sub-Saharan Africa, which was addressed through horizon scanning. Utilising the CABI Horizon Scanning Tool, 8,747 non-native pest species not previously recorded in Burundi were identified. The initial output was filtered to include only species with complete names, resulting in 8,541 species. This was further refined by selecting pests that affected major value chains in Burundi, leading to 1,803 species. Eight species were added from the analysis of the current list of regulated pests for Burundi, along with four soft rot species considered of phytosanitary concern, bringing the total to 1,815. An additional 104 vectors that transmit the assessed species and seven pathogenic organisms transmitted by those species were added, resulting in 1,926 species. The 1,926 pest species, including 416 classified as invasive, comprised 550 arthropods, 153 bacteria, 79 chromista, 518 fungi, 19 molluscs, 141 nematodes, nine protists, 16 viroids, and 437 viruses. The highest recorded overall risk score was 175, attributed to 41 species, while the lowest was 2, associated with 55 species. The majority (n = 1,030; 53%) of the assessed species could solely be introduced as contaminants, whereas the least (n = 347; 18%) were stowaways, and others (n = 435; 23%) could be introduced through multiple pathways. Using agreed-upon criteria for suggesting management actions, 58% (n = 1,123) of the pest species were deemed unsuitable for any action, 18% (n = 350) were recommended for detection surveillance, and 25% (n = 476) were considered for regulation. Additional actions included contingency planning, raising awareness about high-risk pests (risk communication), managing some species through industry involvement, and conducting research to inform phytosanitary measures. These horizon scanning results will be utilised to develop a Register of Priority Pests for Burundi for risk monitoring and to update the list of regulated pests to facilitate trade in Burundi.